Perlindungan Dan Pemulihan Hak Korban Tindak Pidana: Studi Viktimologi Dalam Sistem Peradilan Pidana Di Indonesia - Rachelya Putri Audrian; Lusya Najwa Vesca H; Ria Anggraeni Utami (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This study analyzes the protection and restoration of the rights of victims of crime through a victimology perspective in the Indonesian criminal justice system, which is still centered on the perpetrator. Using a qualitative approach with a normative-empirical analysis of Law No. 13/2006 concerning Protection of Witnesses and Victims (PSK Law), KMA Regulation No. 4/2013, and restorative justice practices, this study reveals systemic weaknesses such as minimal financial compensation, slow psychosocial rehabilitation, and low victim participation in the judicial process. The study also shows that only a small proportion of victims receive adequate restorative rights, with significant disparities between types of crimes of sexual violence, corruption, and narcotics. Women and child victims are the most vulnerable groups due to secondary victimization from the formal legal process. The study recommends reforms through: (1) strengthening the Witness and Victim Protection Agency (LPSK) with direct executive authority, (2) integrating mandatory victim impact statements into judges' deliberations, (3) developing a digital-based one-stop center for integrated recovery, and (4) harmonizing restorative justice with a victimology approach based on victims' rights. This reform is expected to realize substantive justice that sides with victims as legal subjects, not merely passive witnesses in the Indonesian criminal justice system.